Pengaruh Sistem Reward, Digitalisasi, Dan Metode Kampanye Audio-Visual Terhadap Tingkat Kepedulian Keselamatan Pekerja - Zia Ulhaq; Erna Indriastiningsih; Yunita Primasanti (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
XYZ is a multi-disciplinary company operating in the fields of mining contracts, engineering, procurement and construction as well as oil and gas services. This business entity, which has been established since 1972, has a strong commitment to Occupational Safety and Health (K3) which has become a culture in every element of the company. Basically, K3 is an effort to prevent/avoid/reduce accidents by stopping/removing/eliminating risks (risks). K3 is one of the requirements for increasing employee work productivity, this is closely related to achieving work or production targets. This research was conducted at the company PT. XYZ in the Balikpapan area. The aim of this research is to measure the level of employee concern for K3, with the efforts that the company has made through the rewards system, digitalization and audio-visual campaign methods. The research population is employees of PT. XYZ in the Balikpapan area. Sampling was carried out using a two-stage multi-stage cluster random sampling technique. The first stage is separated based on department cluster; Asset Management, SHE, SCM, HCBS, and Finance. The second stage is PT employees. XYZ is separated based on work environment stratification; office and field. Respondent data was analyzed with SEM-PLS using Smart PLS 3.0 software. The model developed illustrates that the rewards system, digitalization and audio-visual campaigns have a positive influence on worker safety motivation and indirectly influence worker safety behavior through worker safety motivation which acts as a mediating variable. Meanwhile, work safety motivation has a positive effect on work safety behavior.